2010
DOI: 10.1021/cm100023p
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Silver Nanoparticles Increases during Storage Because of Slow Dissolution under Release of Silver Ions

Abstract: The dissolution of citrate-stabilized and poly(vinylpyrrolidone)-stabilized silver nanoparticles in water was studied by dialysis for up to 125 days at 5, 25, and 37 °C. The particles slowly dissolve into ions on a time scale of several days. However, in all cases, a limiting value of the released silver was observed, i.e., the particles did not completely dissolve. In some cases, the nanoparticles released up to 90% of their weight. Formal kinetic data were computed. Rate and degree of dissolution depended on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
823
6
10

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,033 publications
(897 citation statements)
references
References 23 publications
58
823
6
10
Order By: Relevance
“…The rate constants increased linearly between 0.01 and 0.10 d -1 over the 10-550 mM NaCl range. These first-order rate constants are lower than rate constants reported in previous studies on AgNP dissolution, which is contrary to expectations because the catalytic effect of NaCl is absent from the previous studies; [18][19][20] however, mass-based rate constants are not always comparable for surface-mediated reactions.…”
Section: Dissolution Ratescontrasting
confidence: 94%
See 3 more Smart Citations
“…The rate constants increased linearly between 0.01 and 0.10 d -1 over the 10-550 mM NaCl range. These first-order rate constants are lower than rate constants reported in previous studies on AgNP dissolution, which is contrary to expectations because the catalytic effect of NaCl is absent from the previous studies; [18][19][20] however, mass-based rate constants are not always comparable for surface-mediated reactions.…”
Section: Dissolution Ratescontrasting
confidence: 94%
“…It has also been reported that AgNPs achieve a pseudo-equilibrium that is dependent on the initial AgNP concentration and size, a hypothesis explained by citing the size-dependent thermodynamic properties of AgNPs, 19,20 and that mass-based AgNP dissolution rate constants decreased as the concentration of AgNPs increased. 18,19 Both these phenomena could be caused by the depletion of molecular oxygen and hydrogen ions; 18,20 however, this possibility does not appear to hold in at least one case where these trends are apparent. 19 Another interpretation is that aggregation and dissolution act as competing processes, both of which depend on initial nanoparticle concentration and size.…”
Section: Dissolution Ratesmentioning
confidence: 98%
See 2 more Smart Citations
“…To our knowledge, only three studies evaluated AgNP dissolution over a time course of several months. 12,13,29 The first study predicts that AgNPs will not persist in an oxic solution and will undergo complete oxidative dissolution. 12 Thermodynamic calculations suggest that the oxidative dissolution of AgNPs should proceed to completion under oxic conditions.…”
Section: ■ Introductionmentioning
confidence: 99%